Juridical Review : Labor Wage Regulations In Indonesia Legislation (Case of Undang-Undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan dan Undang-Undang Nomor 11 Tahun 2020 tentang Cipta Kerja) - Muhammad Iqbal Baiquni; Tri Sulistyono (Jurnal Dialektika Hukum, 2021)
The right to get a job and a decent life is a basic right of every citizen that has been mandated by the constitution. However, in its application there are various problems in employment, one of which is related to the right to wages. Wage problems occur because existing regulations have not been able to provide protection for their rights. Therefore, the Government must act to make changes and harmony in realizing the rights of citizens to just and constitutionally decent wages. In this paper, the author uses juridical-normative research with a statue approach in finding and analyzing the Law on Employment and Job Creation. This article is the result of an analysis of wage protection arrangements in accordance with existing laws and legal principles